Re-evaluating the Marketing Mix: An Empirical Study on the Indirect Influence of the 4Ps on Purchase Intention via Customer Attitude - Dhimas Samudra Firmansyah; Liliana Dewi (Jurnal Bisnis dan Manajemen, 2026)
In the hyper-competitive fashion retail landscape, reliance on the traditional 4P Marketing Mix framework often fails to effectively shape consumer attitudes, necessitating a re-evaluation of the drivers of purchase intention. This study critically analyses the influence of the Marketing Mix (Product, Price, Place, and Promotion) on Purchase Intention with Customer Attitude as a mediating variable among consumers of CPB Clothes Royal Plaza Surabaya. Using a quantitative approach through a survey, data were collected from 220 prospective male consumers selected using a purposive sampling technique. Data analysis was conducted using Structural Equation Modelling–Partial Least Square (SEM-PLS) with bootstrapping for hypothesis testing. The results revealed significant findings: the 4PD Marketing Mix elements did not show a statistically significant influence on Customer Attitude. Conversely, Customer Attitude proved to be a positive and significant predictor of Purchase Intention. The low R-square value confirmed that the 4P framework had a limited contribution, indicating that other factors such as shopping experience and brand image played a more dominant role. These findings provide crucial strategic implications for practitioners to shift from 4P-based strategies towards creating superior customer experiences as the key to building positive attitudes and driving strong purchase intentions.